Analysts’ Forecasts and Stock Prices in Nigeria - Onipe Yahaya (Iranian Journal of Accounting, Auditing & Finance, 2021)
Analyst forecast information is available to the public in less developed countries at a little cost. The role of analysts in forecasting stock returns cannot be over-emphasized. Yet, little scholarly works have been done in Nigeria. The purpose of this paper is to interrogate analysts’ forecasts' effect on share prices in Nigeria. The research approach is correlational. We collected and analyzed data for several years from the annual reports and accounts of 138 corporations over 10 years (2010-2019). The results indicate that experts 1, 3, and 4 have a significant and positive impact on stock return. The information from expert 2 had failed to show any signal of significance. Based on the majority of these results, the paper recommends that financial analysts consider the information when considering the price of stocks in Nigeria. The conclusion is that the study results have implications for stakeholders (management, public, employees, suppliers, investors, creditors, regulators, governments, customers, users, partners, charity organizations, special interest-holders; competitors, community groups, trade groups, and the media/press) and based on the findings, it is suggested among others that stakeholders who need the prices of stocks should depend on analyst forecast.